2017
DOI: 10.1002/adsc.201700202
|View full text |Cite
|
Sign up to set email alerts
|

Metal Substitution Modulates the Reactivity and Extends the Reaction Scope of Myoglobin Carbene Transfer Catalysts

Abstract: Engineered myoglobins have recently emerged as promising scaffolds for catalyzing carbene-mediated transformations. In this work, we investigated the effect of altering the metal center and its first-sphere coordination environment on the carbene transfer reactivity of myoglobin. To this end, we first established an efficient protocol for the recombinant expression of myoglobin variants incorporating metalloporphyrins with non-native metals, including second- and third-row transition metals (ruthenium, rhodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
111
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 56 publications
2
111
0
Order By: Relevance
“…In agreement with previous observations, 9 the presence of oxygen significantly reduces the catalytic activity of Mb(H64V,V68A), which exhibits only ~430 TON for the formation of 5 (Entry 3, Table 1) compared to >10,000 TON 6a under oxygen-free conditions. The stereoselectivity of the transformation is also affected (98% de and 95% ee vs. >99.9% de and ee ).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous observations, 9 the presence of oxygen significantly reduces the catalytic activity of Mb(H64V,V68A), which exhibits only ~430 TON for the formation of 5 (Entry 3, Table 1) compared to >10,000 TON 6a under oxygen-free conditions. The stereoselectivity of the transformation is also affected (98% de and 95% ee vs. >99.9% de and ee ).…”
supporting
confidence: 92%
“…6a Since ferrous myoglobin has high affinity for oxygen, this non-native reactivity is severely suppressed in the presence of air, imposing the need for strictly anaerobic conditions to realize these transformations. While this inhibitory effect is somewhat alleviated by mutations at the level of the distal histidine residue, 9 which is directly involved in stabilizing the oxy-form of myoglobin, 10 the catalytic activity of Mb-based cyclopropanation catalysts is drastically reduced in the presence of oxygen. A similar drawback concerns iron-porphyrins and other synthetic iron-based catalysts previously investigated for cyclopropanation reactions.…”
mentioning
confidence: 99%
“…demonstrated that Mb variants incorporating a non-natural Mn- or Co-porphyrin IX cofactor catalyze intramolecular C–H amination reactions with sulfonyl azides, with reactivities comparable to their iron-containing counterpart [19]. This work was recently expanded by Sreenilayam et al , who reported the recombinant expression of Mb variants incorporating various first, second and third row transition metal cofactors (Mn, Co, Ru, Rh, Ir) [31]. The resulting Mb variants were catalytically active in cyclopropanation, N-H and S-H insertion reactions albeit with generally reduced efficiency compared to the iron-containing counterparts.…”
Section: New Carbene Transfer Reactions Catalyzed By Engineered Heme mentioning
confidence: 99%
“…These enzymes have proven amenable to optimization by both genetic methods and co‐factor replacement 14, 15, 16, 17, 18, 19, 20. A common feature of these (designed) heme enzymes is that they contain a large hydrophobic substrate binding pocket orthogonal to the plane of the heme moiety.…”
mentioning
confidence: 99%